Memorandum of understanding between Universiti Teknologi MARA and Yayasan Perantau Mahad Muhammadi / Fakulti Pengurusan Maklumat - Universiti Teknologi MARA, Fakulti Pengurusan Maklumat (Universiti Teknologi MARA (UiTM), 2021)
UiTM and Yayasan Perantau Mahad Muhammadi will endeavour to strengthen, promote and develop cooperation on the basis of equality and mutual benefit.